A core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding and its coating, preparation method and application

By adopting nuclear shell structure ceramics@通过 通过 通过 composite powder, the problem of insufficient coating and abrasion resistance in ultra -high -speed laser melting technology is solved, and coating with high hardness, abrasion resistance and toughness is achieved. It is suitable for extremes to extremes Equipment under work conditions.

CN115889769BActive Publication Date: 2025-01-28HOHAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211482007.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-01-28
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

In the existing ultra-high-speed laser cladding technology, the hardness and wear resistance of the coating material are insufficient, and the distribution of ceramic particles in the metal matrix is ​​difficult to control, which can easily lead to cracks and performance differences.

Method used

The nuclear shell structure ceramic@采 采 采 composite powder is used to cover the CR3C2 ceramic core through entropy alloys in Cocrni. The wet chemical reduction technology is used to prepare the composite powder to ensure the uniform distribution of the ceramic particles and the alloy covering layer and the ceramic.

Benefits of technology

A coating of crackless defects, uniform distribution of ceramic phase, good toughness and high hardness, suitable for aerospace, water conservancy ocean and national defense technology equipment under extreme conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115889769B_ABST
    Figure CN115889769B_ABST
Patent Text Reader

Abstract

The present invention discloses a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding, and its coating, preparation method and application. The composite powder is composed of a Cr3C2 ceramic core coated with a CoCrNi medium entropy alloy as a shell material. The present invention adopts a high-hardness Cr3C2 ceramic particle of a coated core-shell powder structure and a high-toughness medium entropy FCC face-centered cubic phase for synergistic compounding. Through a reasonable component ratio design and an ultra-high-speed laser in-situ two-step process, the technical problem of easy cracking of existing metal ceramic powders during the rapid melting process of ultra-high-speed laser cladding is solved, and the efficient preparation of a crack-free, high-ceramic content and strong and tough integrated composite coating is achieved; and the entire process flow is completed by laser integration, which greatly improves the preparation and production efficiency, and is conducive to industrial development; it can be used for the manufacture and operation and maintenance of key parts of equipment in the fields of aerospace, water conservancy, ocean, national defense science and technology, etc. that serve under extreme working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding and a coating, a preparation method and application thereof, belonging to the technical field of material surface engineering and remanufacturing. Background Art

[0002] As an emerging advanced surface engineering technology, ultra-high-speed laser cladding has the advantages of high preparation efficiency, high powder utilization, high coating surface accuracy, low dilution rate, small heat-affected zone, thin coating thickness, and metallurgical bonding between coating and substrate. It may become a revolutionary alternative technology for traditional coating technology. At the same time, its environmental advantages of green energy saving and environmental protection and good economic benefits make it have great application potential in the protection and remanufacturing of high-end equipment in the fields of aviation, aerospace, automobile, ocean, energy, etc. However, at present, most of the materials reported for ultra-high-speed laser cladding coatings are traditional laser cladding or thermal spraying powder materials, and the material system is relatively single, such as self-fluxing alloys, iron-based alloys, nickel-based alloys, Stellite cobalt-based alloys, etc., which can no longer meet the performance requirements of long-life service of equipment under extreme working conditions. Its insufficient quality and shortage of types have become the "bottleneck" restricting the development of ultra-high-speed laser cladding technology. At present, there is still a lack of special series and refined powder systems for the characteristics of ultra-high-speed laser cladding technology. Therefore, it is of great significance to study and develop a new ultra-high-speed laser cladding special powder system that matches its characteristics for its vigorous promotion and application.

[0003] In recent years, CrCoNi medium-entropy alloys with outstanding ductility and damage resistance have better work hardening and strong-plastic balance capabilities than high-entropy alloys and most multiphase alloys. It is a new material with great potential for engineering applications. The use of rapid melting laser manufacturing technology can help improve the dislocation density of CrCoNi medium-entropy alloys and promote the formation of cellular structure, making them have better mechanical properties, higher efficiency and better versatility. The Korea Atomic Energy Research Institute successfully prepared a CrCoNi medium-entropy alloy with a yield strength, tensile strength and elongation of 490 MPa, 800 MPa and 57% respectively through direct laser energy deposition technology; however, a recent study by Shanghai Jiaotong University showed that the maximum hardness of the CrCoNi medium-entropy alloy manufactured by selective laser additive manufacturing is only 245.6 HV 0.3, the low hardness limits its wide application under extreme working conditions. In order to improve the hardness and wear resistance of medium-entropy alloy coatings, ceramic composite is a quick and effective technical approach. At present, ceramic composite methods are mainly through two methods: in-situ self-generation of precursor powder and ball milling mixing. However, due to the difference in the physicochemical properties of metal and ceramic powders, the distribution of ceramic particles in the metal matrix during the subsequent molding process is difficult to control, and they are segregated in agglomeration, resulting in differences in their internal properties, resulting in uneven stress, thereby causing premature failure. At the same time, the small spot density and large cladding line speed of ultra-high-speed laser cladding make the cladding layer in an extremely hot and cold state. At a high ceramic content, it will cause a large residual stress in the cladding layer, causing the cladding layer to crack easily, which directly affects the coating performance. Therefore, it is of great engineering significance to develop a ceramic / medium-entropy alloy composite powder with uniform composition, controllable particle size, good fluidity, and balanced strength and toughness for ultra-high-speed laser cladding. Summary of the invention

[0004] Purpose of the invention: In order to solve the above problems, the purpose of the present invention is to provide a core-shell structure ceramic @ medium-entropy alloy composite powder for ultra-high-speed laser cladding, which is composed of a Cr3C2 ceramic core coated with a CoCrNi medium-entropy alloy as a shell material, which significantly improves the hardness and wear resistance of the medium-entropy alloy coating.

[0005] At the same time, the present invention provides a method for preparing core-shell structure ceramic@medium entropy alloy composite powder for ultra-high speed laser cladding, and takes wet chemical reduction technology to prepare core-shell structure composite powder as the entry point. The composite powder synthesized by this method has the advantages of uniform distribution of CrCoNi medium entropy alloy on the surface of Cr3C2 ceramic particles, controllable content, strong bonding force between alloy coating layer and ceramic, low impurity content, etc. Under the conditions of ultra-high speed laser cladding rapid melting, it can form a cladding deposition layer with no crack defects, uniform distribution of ceramic phase, good toughness and high hardness.

[0006] At the same time, the present invention provides a coating obtained by ultra-high-speed laser cladding using core-shell structure ceramic@medium entropy alloy composite powder, the coating has no crack defects and has uniform ceramic phase distribution, good toughness and high hardness.

[0007] At the same time, the present invention provides a method for preparing a coating obtained by ultra-high-speed laser cladding using core-shell structure ceramic@medium-entropy alloy composite powder. Under the conditions of ultra-high-speed laser cladding with small spot density and large cladding line speed, the cladding layer is in an extremely hot or cold state. Under a high ceramic content, no large residual stress is generated in the cladding layer, the cladding layer is not easy to crack, and the coating performance is excellent.

[0008] At the same time, the present invention provides a coating obtained by ultra-high-speed laser cladding using core-shell structure ceramic@medium entropy alloy composite powder for application in key components of aerospace, water conservancy, ocean, and national defense science and technology equipment such as blades, shafts, piston rods, transmission system gears, stern shafts (tail shafts), drill bits, and drill rods.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0010] A core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding, wherein the composite powder is composed of a Cr3C2 ceramic core coated with a CoCrNi medium entropy alloy as a shell material.

[0011] The mass ratio of the CoCrNi medium entropy alloy to the Cr3C2 ceramic powder is 2:1-4:1.

[0012] The molar ratio of the elements in the CoCrNi mesentropy alloy is: Co:Cr:Ni=(1-2):(1-2):(1-3).

[0013] A method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding comprises the following steps:

[0014] S01, pretreatment of Cr3C2 ceramic particles: add 100g of Cr3C2 ceramic particles to a solution containing 5-10% HF and 10-15% HCl, perform ultrasonic roughening treatment for 4-6min, filter and wash with distilled water until the filtrate is neutral; then put the roughened Cr3C2 ceramic particles into an activation sensitization solution for ultrasonic treatment for 30-50min, after the pretreatment is completed, wash the Cr3C2 ceramic particles and dry them for plating;

[0015] S02, nickel-cobalt-chromium plating: put the powder to be plated into a stirred reactor with a volume of >1L, add 1L of a solution containing 25-100g / L nickel salt, 25-65g / L cobalt salt, 25-60g / L chromium salt and 20-50g / L reducing agent, heat to 80-90°C in a water bath, control the pH value to 9-12, and react for 60-120min. Plate the metal coating layer through an autocatalytic reaction to obtain a CoCrNi medium entropy alloy coated chromium carbide composite powder with a particle size distribution range of 47-70μm and a fluidity of 50-80s / 100g. The solvent is deionized water.

[0016] The activation sensitization solution comprises the following components: palladium chloride PdCl2 0.3-0.5 g / L, hydrochloric acid HCl 60-70 mL / L, stannous chloride SnCl2·2H2O 20-30 g / L and sodium chloride NaCl 140-160 g / L.

[0017] The nickel salt includes one or more of nickel chloride, nickel sulfate, nickel bromide and nickel iodide; the cobalt salt includes one or more of cobalt chloride, cobalt sulfate, cobalt bromide and cobalt iodide; the chromium salt includes one or more of chromium chloride, chromium sulfate, chromium bromide and chromium iodide; the reducing agent includes one or more of sodium hypophosphite, hydrazine hydrate and sodium borohydride.

[0018] A coating is obtained by ultra-high-speed laser cladding using core-shell structure ceramic@medium entropy alloy composite powder. The coating has a thickness of 100-300 μm, and the structure of the coating consists of an FCC phase and a Cr3C2 ceramic phase; the average Vickers hardness is ≥800 Hv.

[0019] A method for preparing a coating obtained by ultra-high-speed laser cladding using core-shell structure ceramic@medium entropy alloy composite powder comprises the following steps:

[0020] The first step is to use an ultra-high-speed laser beam to scan the surface of the degreased and cleaned metal substrate within the set parameter range until the surface temperature of the metal substrate reaches 150-200°C; the set parameters are: laser power 300-500W, spot diameter 1.0-3.0mm, laser scanning speed 80-100mm / s;

[0021] In the second step, the composite powder is clad on the surface of the metal substrate using ultra-high-speed laser cladding technology under preset process parameters, and after natural cooling, the deposition coating is prepared; the preset process parameters are: laser power of 1500~3500W, spot diameter of 0.6~1.2mm, powder feeding rate of 1.5~3 kg / h, laser scanning speed of 80~120mm / s, and overlap rate of 50~65%.

[0022] The metal matrix includes carbon steel, stainless steel, aluminum alloy or nickel alloy.

[0023] The coating is used in key components of aerospace, water conservancy, ocean, and national defense science and technology equipment, and the key components include shaft parts, piston rods, transmission system gears, stern shafts, tail shafts, or drill bits and drill rods.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0025] (1) Aiming at the ultra-high-speed laser cladding process, the present invention proposes a composite powder design concept of "introducing ceramic particles to strengthen the FCC-type medium-entropy alloy system". By in-situ depositing a metal coating layer on the surface of ceramic powder particles, the coating has high integrity and strong bonding with the cross-section of the ceramic particles, thus realizing the design and preparation of high-strength and tough core-shell structural ceramic@medium-entropy alloy composite powders.

[0026] (2) Through the reasonable design of component ratio, the use of strong and tough balanced coated core-shell composite powder structure and ultra-high-speed laser in-situ two-step process, the problem of easy cracking of existing metal ceramic powders during the rapid melting process of ultra-high-speed laser cladding is effectively avoided, and the efficient preparation of CoCrNi medium-entropy alloy composite coatings with dispersed distribution of Cr3C2 particles without crack defects is achieved; and the entire process flow can be completed in an integrated manner using lasers, which greatly improves the preparation production efficiency and is conducive to industrial development.

[0027] (3) The initiation and development of cracks in the coating are suppressed and reduced by the load-bearing effect of high-hardness Cr3C2 ceramic particles and the impact and friction force of the high-toughness medium-entropy FCC face-centered cubic phase absorption coating. In addition, the two have good matching physical and chemical properties, and the strong and tough integration of the coating with a high ceramic content is achieved. It can be used for the manufacture and operation and maintenance of key components of equipment in the fields of aerospace, water conservancy, ocean, national defense science and technology, etc. that serve under extreme working conditions. It has important economic value and promotion significance.

[0028] The present invention adopts high-hardness Cr3C2 ceramic particles of a coated core-shell powder structure and high-toughness medium-entropy FCC face-centered cubic phase for synergistic compounding. Through reasonable component ratio design and ultra-high-speed laser in-situ two-step process, the technical problem of easy cracking of existing metal ceramic powders during ultra-high-speed laser cladding rapid melting process is solved, and efficient preparation of crack-free, high-ceramic content and strong and tough integrated composite coatings is achieved; and the entire process flow can be completed in an integrated manner using a laser, which greatly improves the preparation production efficiency and is conducive to industrial development; it can be used for the manufacture and operation and maintenance of key components of equipment in the fields of aerospace, water conservancy, ocean, national defense science and technology, etc. that serve under extreme working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the appearance morphology of the core-shell composite powder prepared in Example 1;

[0030] Figure 2 This is a cross-sectional morphology of the core-shell composite powder prepared in Example 1;

[0031] Figure 3 is the X-ray diffraction pattern of the composite powder prepared in Example 1;

[0032] Figure 4 is a cross-sectional morphology of the coating prepared in Example 2;

[0033] Figure 5 is the X-ray diffraction pattern of the coating prepared in Example 3;

[0034] Figure 6 is the cross-sectional hardness distribution of the coating prepared in Example 4. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0036] Unless otherwise specified, other materials and raw materials used in the present invention are conventional raw materials that can be purchased from the market. The technical means used are conventional means well known to those skilled in the art.

[0037] The test method used in the embodiment is as follows:

[0038] (1) The physical structure of the prepared samples was determined using an X-ray diffractometer.

[0039] (2) The morphology of the prepared powders was observed using a scanning electron microscope.

[0040] (3) Use a stereo microscope to observe the cross-sectional morphology of the coating.

[0041] (4) The microhardness of the coating was measured using a Vickers hardness tester.

[0042] Example 1

[0043] A method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding, the steps are as follows: first, weigh 100g of Cr3C2 ceramic particles and pre-treat them, and the specific steps are as follows: add the Cr3C2 ceramic particles to a solution containing 10% HF and 10% HCl, ultrasonically roughen them for 5 minutes, filter them and wash them with distilled water for 3 times until the filtrate is neutral; then put the roughened Cr3C2 ceramic particles into an activation sensitization solution for ultrasonic treatment for 30 minutes, and the specific components of the activation sensitization solution are palladium chloride (PdCl2) 0.5g / L, hydrochloric acid (HCl) 60mL / L, stannous chloride (SnCl2·2H2O) 20g / L, and sodium chloride (NaCl) 160g / L. After the pre-treatment is completed, the Cr3C2 ceramic particles are washed several times and dried for plating. Nickel-cobalt-chromium layer plating: put the above-mentioned powder to be plated into a 1.5L stirred reactor, add 25g / L nickel chloride as nickel salt, 25g / L cobalt chloride as cobalt salt and 25g / L chromium chloride as chromium salt raw material, and 1L of 20g / L sodium hypophosphite as reducing agent, heat to 80°C in a water bath, control the pH value to 10, and react for 60min. Plate the metal coating layer through autocatalytic reaction to obtain chromium-cobalt-nickel coated chromium carbide composite powder, wherein the mass ratio of metal to ceramic is 2:1, and the molar ratio of the element composition of the entropy alloy in CoCrNi is 1:1:1. The appearance morphology of the prepared composite powder is as follows: Figure 1As shown, the composite powder is approximately spherical in appearance, with an average powder diameter of 47 μm. Its fluidity is 50 s / 100 g. The cross-sectional morphology of the composite powder is shown in Figure 2 As shown in FIG. 1 , the composite powder has a core-shell structure, and the metal coating layer is dense and complete. The composite powder is subjected to XRD phase analysis using an X-ray diffractometer, and the results are as follows: Figure 3 As shown, the composite powder is a single FCC phase, which further confirms the core-shell structure of the composite powder.

[0044] A core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding, wherein the composite powder is composed of a Cr3C2 ceramic core coated with a CoCrNi medium entropy alloy as a shell material.

[0045] The coating obtained by using the core-shell structure ceramic@medium entropy alloy composite powder by ultra-high speed laser cladding of this embodiment has a structure composed of an FCC phase and a Cr3C2 ceramic phase.

[0046] A method for preparing a coating obtained by ultra-high-speed laser cladding with a core-shell structure ceramic @ medium entropy alloy composite powder, the steps are as follows: first, use an ultra-high-speed laser beam to scan the surface of the substrate after degreasing and decontamination until the surface temperature of the substrate reaches 200°C. The scanning process parameters are as follows: laser power 300W, spot diameter 3.0mm, laser scanning speed 80mm / s. Then, the ultra-high-speed laser cladding technology is used to clad the above-mentioned core-shell structure Cr3C2 / CoCrNi composite powder on the surface of the above-mentioned substrate under the process parameters of power 1500W, spot diameter 0.6mm, powder feeding rate 2kg / h, laser scanning rate 100mm / s, and overlap rate 50%. After natural cooling, the high-quality coating preparation can be completed.

[0047] The substrate is a metal substrate, including single metals and alloys such as carbon steel, stainless steel, aluminum alloy or nickel alloy, which will not be described in detail here.

[0048] The coating obtained in this embodiment is used in key parts of aerospace, water conservancy, ocean, and national defense science and technology equipment, such as shaft parts, piston rods, transmission system gears, stern shafts (tail shafts), drill bits and drill rods, etc.

[0049] Example 2

[0050] A method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding, the steps are as follows: first, weigh 100g of Cr3C2 ceramic particles and pre-treat them, the specific steps are as follows: add the Cr3C2 ceramic particles to a solution containing 10% HF and 10% HCl, ultrasonically disperse them for 6 minutes, filter and wash them with distilled water for 3 times until the filtrate is neutral; then put the coarsened Cr3C2 ceramic particles into an activation sensitization solution for ultrasonic treatment for 40 minutes, the specific components of the activation sensitization solution are palladium chloride (PdCl2) 0.3g / L, hydrochloric acid (HCl) 60mL / L, stannous chloride (SnCl2·2H2O) 20g / L, sodium chloride (NaCl) 140g / L. After the pre-treatment is completed, the Cr3C2 ceramic particles are washed several times and dried for plating. Nickel cobalt chromium layer plating: the above-mentioned powder to be plated is placed in a 1.5L stirred reactor, 30g / L nickel sulfate, 35g / L nickel chloride and 35g / L nickel bromide are added as nickel salts, 25g / L cobalt sulfate is cobalt salt, 25g / L chromium sulfate and 30g / L chromium chloride are added as chromium salt raw materials, and the reducing agent is 20g / L hydrazine hydrate and 25g / L sodium borohydride, a total of 1L, heated to 90°C in a water bath, the pH value is controlled to 12, the reaction time is 120min, and the metal coating layer is plated by autocatalytic reaction to obtain a chromium cobalt nickel coated chromium carbide composite powder, wherein the mass ratio of metal to ceramic is 4:1, and the molar ratio of the element composition of the entropy alloy in CoCrNi is 1:2:3. The average powder diameter of the prepared composite powder is 70μm. Its fluidity is 80s / 100g. The composite powder was subjected to XRD phase analysis using an X-ray diffractometer. The composite powder was a single FCC phase, indicating that the powder had a complete core-shell structure.

[0051] A method for preparing a coating obtained by ultra-high-speed laser cladding using core-shell structure ceramic @ medium-entropy alloy composite powder, the steps are as follows: first, use an ultra-high-speed laser beam to scan the surface of the substrate after degreasing and decontamination until the surface temperature of the substrate reaches 150°C. The scanning process parameters are as follows: laser power 400W, spot diameter 2.5mm, laser scanning speed 100mm / s. Then, using ultra-high-speed laser cladding technology, the Cr3C2 / CoCrNi composite powder with the core-shell structure is clad on the surface of the above-mentioned substrate under the process parameters of power 2000W, spot diameter 0.8mm, powder feeding rate 1.5kg / h, laser scanning rate 80mm / s, and overlap rate 65%. After natural cooling, the high-quality coating preparation is completed. The cross-sectional morphology of the prepared coating was analyzed using an Olympus stereo microscope, and the results are as follows. Figure 4 As shown, it can be seen that the coating has a thickness of about 200 μm, has no crack defects, and forms a good metallurgical bond with the substrate. The hardness of the coating is tested using a microhardness tester, and its average hardness is 820 HV.

[0052] Example 3

[0053] A method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding, the steps are as follows: first, weigh 100g of Cr3C2 ceramic particles and pre-treat them, the specific steps are as follows: add the Cr3C2 ceramic particles to a solution containing 10% HF and 10% HCl, ultrasonically disperse them for 5 minutes, filter and wash them with distilled water for 3 times until the filtrate is neutral; then put the coarsened Cr3C2 ceramic particles into an activation sensitization solution for ultrasonic treatment for 30 minutes, the specific components of the activation sensitization solution are palladium chloride (PdCl2) 0.4g / L, hydrochloric acid (HCl) 60mL / L, stannous chloride (SnCl2·2H2O) 20g / L, sodium chloride (NaCl) 160g / L. After the pre-treatment is completed, the Cr3C2 ceramic particles are washed several times and dried for plating. Nickel cobalt chromium layer plating: the above-mentioned powder to be plated is placed in a 1.5L stirred reactor, 35g / L nickel bromide is added as nickel salt, 35g / L cobalt bromide and 30g / L cobalt chloride are added as cobalt salt, 35g / L chromium bromide and 25g / L chromium chloride are added as chromium salt raw materials, and the reducing agent is 35 g / L sodium borohydride, a total of 1L deionized water solution, heated to 85°C in a water bath, the pH value is controlled to be 11, the reaction time is 100min, and the metal coating layer is plated by autocatalytic reaction to obtain a chromium cobalt nickel coated chromium carbide composite powder, wherein the mass ratio of metal to ceramic is 2:1, and the molar ratio of the element composition of the entropy alloy in CoCrNi is 2:2:1. The average diameter of the prepared composite powder is 56μm. Its fluidity is 56s / 100g. The composite powder is subjected to XRD phase analysis by an X-ray diffractometer, and the composite powder is a single FCC phase, indicating that the powder is a complete core-shell structure.

[0054] A method for preparing a coating obtained by ultra-high-speed laser cladding using a core-shell structure ceramic @ medium entropy alloy composite powder, the steps are as follows: first, use an ultra-high-speed laser beam to scan the surface of the substrate after degreasing and decontamination until the surface temperature of the substrate reaches 175°C. The scanning process parameters are as follows: laser power 500W, spot diameter 1.0mm, laser scanning speed 90mm / s. Then, the ultra-high-speed laser cladding technology is used to clad the above-mentioned core-shell structure Cr3C2 / CoCrNi composite powder on the surface of the above-mentioned substrate under the process parameters of power 3500W, spot diameter 1.2mm, powder feeding rate 3kg / h, laser scanning rate 120mm / s, and overlap rate 55%. After natural cooling, the high-quality coating preparation is completed. The cross-sectional morphology of the prepared coating is analyzed using an Olympus stereo microscope. The thickness of the coating is about 100μm. The composite coating is subjected to XRD phase analysis using an X-ray diffractometer, and the results are as follows Figure 5As shown, the coating structure consists of FCC face-centered cubic phase and Cr3C2 ceramic phase. The hardness of the coating is tested using a microhardness tester, and the average hardness is 850HV.

[0055] Example 4

[0056] A method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding, the steps are as follows: first, weigh 100g of Cr3C2 ceramic particles and pre-treat them, the specific steps are as follows: add the Cr3C2 ceramic particles to a solution containing 10% HF and 10% HCl, ultrasonically disperse them for 4 minutes, filter and wash them with distilled water for 3 times until the filtrate is neutral; then put the coarsened Cr3C2 ceramic particles into an activation sensitization solution for ultrasonic treatment for 50 minutes, the specific components of the activation sensitization solution are palladium chloride (PdCl2) 0.5g / L, hydrochloric acid (HCl) 60mL / L, stannous chloride (SnCl2·2H2O) 20g / L, sodium chloride (NaCl) 160g / L. After the pre-treatment is completed, the Cr3C2 ceramic particles are washed several times and dried for plating. Nickel-cobalt-chromium layer plating: the above-mentioned powder to be plated is placed in a 1.5L stirred reactor, 34g / L nickel iodide, 30g / L nickel bromide and 20g / L nickel chloride are added as nickel salts, 20g / L cobalt iodide and 35g / L cobalt chloride are added as cobalt salts, 35g / L chromium iodide is added as chromium salt raw material, the reducing agent is 25g / L hydrazine hydrate and 25g / L sodium hypophosphite, the water bath is heated to 80°C, the pH value is controlled to 9, the reaction time is 110min, and the metal coating layer is plated by autocatalytic reaction to obtain a chromium-cobalt-nickel coated chromium carbide composite powder, wherein the mass ratio of metal to ceramic is 3:1, and the molar ratio of the element composition of the entropy alloy in CoCrNi is 2:1:3. The average diameter of the prepared composite powder is 63μm. Its fluidity is 65s / 100g. The composite powder was subjected to XRD phase analysis using an X-ray diffractometer. The composite powder was a single FCC phase, indicating that the powder had a complete core-shell structure.

[0057] A method for preparing a coating obtained by ultra-high-speed laser cladding with a core-shell structure ceramic @ medium entropy alloy composite powder, the steps are as follows: first, use an ultra-high-speed laser beam to scan the surface of a substrate after degreasing and decontamination until the surface temperature of the substrate reaches 200°C. The scanning process parameters are as follows: laser power 400W, spot diameter 3.0mm, laser scanning speed 90mm / s. Then, the Cr3C2 / CoCrNi composite powder with the shell-core structure is clad on the surface of the substrate using ultra-high-speed laser cladding technology under the process parameters of power 2500W, spot diameter 0.6mm, powder feeding rate 2.5kg / h, laser scanning rate 110mm / s, and overlap rate 55%. After natural cooling, the high-quality coating preparation can be completed. The cross-sectional morphology of the prepared coating is analyzed using an Olympus stereo microscope. The thickness of the coating is about 150μm. The composite coating is subjected to XRD phase analysis using an X-ray diffractometer, and its structure consists of an FCC face-centered cubic phase and a Cr3C2 ceramic phase. The hardness of the coating was tested using a microhardness tester. The results are as follows: Figure 6 As shown, its average hardness is 875HV.

[0058] Example 5

[0059] The difference between this embodiment and embodiment 1 is only that:

[0060] Pretreatment of Cr3C2 ceramic particles: 100 g of Cr3C2 ceramic particles were added into a solution containing 5% HF and 15% HCl.

[0061] The components of the activation sensitization solution are: palladium chloride PdCl2 0.4 g / L, hydrochloric acid HCl 70 mL / L, stannous chloride SnCl2·2H2O 30 g / L and sodium chloride NaCl 150 g / L.

[0062] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.

[0063] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.

[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding, characterized in that: The composite powder is composed of a Cr3C2 ceramic core coated with a CoCrNi medium entropy alloy as a shell material; The preparation method comprises the following steps: S01, pretreatment of Cr3C2 ceramic particles: add 100g of Cr3C2 ceramic particles to a solution containing 5-10% HF and 10-15% HCl, perform ultrasonic roughening treatment for 4-6min, filter and wash with distilled water until the filtrate is neutral; then put the roughened Cr3C2 ceramic particles into an activation sensitization solution for ultrasonic treatment for 30-50min, after the pretreatment is completed, wash the Cr3C2 ceramic particles and dry them for plating; S02, nickel-cobalt-chromium layer plating: put the powder to be plated into a stirred reactor with a volume of >1L, add 1L of a solution containing 25~100g / L nickel salt, 25~65g / L cobalt salt, 25~60g / L chromium salt and 20~50g / L reducing agent, heat it in a water bath to 80~90°C, control the pH value to 9~12, and react for 60~120min. Plate the metal coating layer through an autocatalytic reaction to obtain a CoCrNi medium-entropy alloy-coated chromium carbide composite powder with a particle size distribution range of 47~70μm and a fluidity of 50~80s / 100g.

2. The method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding according to claim 1, characterized in that: The mass ratio of the CoCrNi medium entropy alloy to the Cr3C2 ceramic powder is 2:1-4:

1.

3. The method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding according to claim 1, characterized in that: The molar ratio of the elements in the CoCrNi mesentropy alloy is: Co:Cr:Ni=(1-2):(1-2):(1-3).

4. The method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding according to claim 1, characterized in that: The activation sensitization solution comprises the following components: palladium chloride PdCl2 0.3-0.5 g / L, hydrochloric acid HCl 60-70 mL / L, stannous chloride SnCl2·2H2O 20-30 g / L and sodium chloride NaCl 140-160 g / L.

5. The method for preparing a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high-speed laser cladding according to claim 1, characterized in that: The nickel salt includes one or more of nickel chloride, nickel sulfate, nickel bromide and nickel iodide; the cobalt salt includes one or more of cobalt chloride, cobalt sulfate, cobalt bromide and cobalt iodide; the chromium salt includes one or more of chromium chloride, chromium sulfate, chromium bromide and chromium iodide; the reducing agent includes one or more of sodium hypophosphite, hydrazine hydrate and sodium borohydride.

6. A coating obtained by using a core-shell structure ceramic@medium entropy alloy composite powder for ultra-high speed laser cladding according to any one of claims 1 to 5, characterized in that: The coating has a thickness of 100-300 μm, and the structure of the coating consists of an FCC phase and a Cr3C2 ceramic phase; the average Vickers hardness is ≥800 Hv.

7. The method for preparing the coating according to claim 6, characterized in that: The following steps are involved: The first step is to use an ultra-high-speed laser beam to scan the surface of the degreased and cleaned metal substrate within the set parameter range until the surface temperature of the metal substrate reaches 150-200°C; the set parameters are: laser power 300-500W, spot diameter 1.0-3.0mm, laser scanning speed 80-100mm / s; In the second step, the composite powder is clad on the surface of the metal substrate using ultra-high-speed laser cladding technology under preset process parameters, and after natural cooling, the deposition coating is prepared; the preset process parameters are: laser power of 1500~3500W, spot diameter of 0.6~1.2mm, powder feeding rate of 1.5~3 kg / h, laser scanning speed of 80~120mm / s, and overlap rate of 50~65%.

8. The method for preparing the coating according to claim 7, characterized in that: The metal matrix includes carbon steel, stainless steel, aluminum alloy or nickel alloy.

9. Application of the coating according to claim 6 in key parts of aerospace, water conservancy, ocean, and national defense science and technology equipment, characterized in that: The key components include shaft parts, piston rods, transmission system gears, stern shafts, tail shafts or drill bits and drill rods.

Citation Information

Patent Citations

  • Cobalt-chromium-tungsten alloy coated tantalum carbide powder and preparation method thereof

    CN109848407A

  • CoCrNi medium-entropy alloy / chromium carbide ceramic composite powder as well as preparation method and application thereof

    CN117548671A